4(n-8)+5(-6-2n)=-68

Simple and best practice solution for 4(n-8)+5(-6-2n)=-68 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(n-8)+5(-6-2n)=-68 equation:


Simplifying
4(n + -8) + 5(-6 + -2n) = -68

Reorder the terms:
4(-8 + n) + 5(-6 + -2n) = -68
(-8 * 4 + n * 4) + 5(-6 + -2n) = -68
(-32 + 4n) + 5(-6 + -2n) = -68
-32 + 4n + (-6 * 5 + -2n * 5) = -68
-32 + 4n + (-30 + -10n) = -68

Reorder the terms:
-32 + -30 + 4n + -10n = -68

Combine like terms: -32 + -30 = -62
-62 + 4n + -10n = -68

Combine like terms: 4n + -10n = -6n
-62 + -6n = -68

Solving
-62 + -6n = -68

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '62' to each side of the equation.
-62 + 62 + -6n = -68 + 62

Combine like terms: -62 + 62 = 0
0 + -6n = -68 + 62
-6n = -68 + 62

Combine like terms: -68 + 62 = -6
-6n = -6

Divide each side by '-6'.
n = 1

Simplifying
n = 1

See similar equations:

| 4(n-8)+5(-6-2n)=-69 | | 3x+7=5x-x+0 | | 29=a+7 | | v=15x^3+52x^2+32x | | -12t-28=9t+47-(-4t) | | 3v+4=19 | | x^2+20x+42=0 | | 2x+72=12-3x | | 0.8+0.25x=0 | | 9(x-6)=6-30 | | 4q+-24=12 | | x+9f+10=5j | | 15(3x+1)-243(5x-2)=0 | | 25/x+6=5/6 | | 1n-1=18 | | -9x+7y=2 | | -19w+-20=18 | | c-2y=24 | | -13x+6=-12-9 | | x-2-(3+(7-2x))=-6 | | 0.625x(a-2)=10 | | 5x+2=8x+11 | | x+7+2x+3-40=0 | | 4(4x+25)-3(4x-1)=5(4x-7) | | 2x-(5-(3x+4))=x-5 | | (5c-4c)+(c-3c)= | | 5(12-3x)+x=3(-2x+4) | | x=(x+1)*0.62 | | 0=ln(6x) | | 11=-16+7w | | 79-2x=9-9x | | 4x+9=-54+11x |

Equations solver categories